2014
DOI: 10.1038/mi.2013.45
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-bearing dendritic cells from the sublingual mucosa recirculate to distant systemic lymphoid organs to prime mucosal CD8 T cells

Abstract: Effector T cells are described to be primed in the lymph nodes draining the site of immunization and to recirculate to effector sites. Sublingual immunization generates effector T cells able to disseminate to the genital tract. Herein, we report an alternative mechanism that involves the recirculation of antigen-bearing dendritic cells (DCs) in remote lymphoid organs to prime T cells. Sublingual immunization with a muco-adhesive model antigen unable to diffuse through lymphatic or blood vessels induced genital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Antigen-loaded DCs drain from the sublingual mucosa to local lymph nodes where they prime both B and T lymphocytes. The activated lymphocytes can then leave the site of antigen presentation, enter blood circulation and seed other selected mucosal sites where they can regulate differentiation and maturation of B and T (Th1 & Th2) cells [69]. Figure 4C provides a cartoon representation of the oral cavity as a route of vaccine delivery and summarizes the major delivery barriers.…”
Section: Mucosal Vaccine Delivery - Routes and Barriersmentioning
confidence: 99%
“…Antigen-loaded DCs drain from the sublingual mucosa to local lymph nodes where they prime both B and T lymphocytes. The activated lymphocytes can then leave the site of antigen presentation, enter blood circulation and seed other selected mucosal sites where they can regulate differentiation and maturation of B and T (Th1 & Th2) cells [69]. Figure 4C provides a cartoon representation of the oral cavity as a route of vaccine delivery and summarizes the major delivery barriers.…”
Section: Mucosal Vaccine Delivery - Routes and Barriersmentioning
confidence: 99%
“…We and other authors have shown that the mucosal route of immunization imprints T cells with a mucosal homing program defined by a profile of integrin and chemokine receptors promoting their homing to the site of initial activation. Tumors located at mucosal sites (lung, colorectal, genital, head and neck) are exposed to mucosal immunity, organized within a connecting network called MALT (mucosal-associated lymphoid tissues), which may explain why the intranasal route of immunization may induce a genital immune response via the recirculation of mucosal dendritic cells (12). In the study by Sun and colleagues, a4b7 and CCR9 induced on T cells are necessary for the homing of antitumor-specific T cells to the cervicovaginal tract (1).…”
Section: Induction Of Persistent Intraepithelial Cd8mentioning
confidence: 99%
“…65,66 Indeed, DCs activated at a particular immunization site, recirculate to distant lymphoid organs and induce distant T cell priming, explaining the genital immune response observed after i.n immunization with the B subunit of cholera toxin (CTB) coupled to OVA. 67 In clinical settings, however, an intravaginal boost was required to attract T cells to the genital tract after i.n immunization with the cholera toxin coupled to OVA. 68 Additionally, oral, nasal or intravaginal immunization with CTB were able to induce comparable secreted IgA levels in the vaginal tract but no cellular immune responses.…”
Section: Compartmentalization and Immunity At Distant Mucosal Sitesmentioning
confidence: 99%